A Colonial Tentweb Orbweaver Cyrtophora citricola: EENY535/IN966, rev. 4/2013 - Stange, Lionel A. (EDIS, 2013)
Few species of spiders can be considered truly social, but a greater number of species, particularly web-building spiders, live in close proximity to one another. One species which has become highly successful through a lifestyle of colonial aggregation is the orbweaver Cyrtophora citricola Forskål. This 6-page fact sheet was written by Lionel A. Stange, and published by the UF Department of Entomology and Nematology, October 2012. http://edis.ifas.ufl.edu/in966